Rack1 Controls Parallel Fiber–Purkinje Cell Synaptogenesis and Synaptic Transmission - Yang, Haihong; Yang, Chaojuan; Zhu, Qian; Wei, Mengping; Li, Ying; Cheng, Juanxian; Liu, Fengjiao; Wu, Yan; Zhang, Jiyan; Zhang, Chen; Wu, Haitao (Frontiers in Cellular Neuroscience, 2019)
Purkinje cells (PCs) in the cerebellum receive two excitatory afferents including granule cells-derived parallel fiber (PF) and the climbing fiber. Scaffolding protein Rack1 is highly expressed in the cerebellar PCs. Here, we found delayed formation of specific cerebellar vermis lobule and impaired motor coordination in PC-specific Rack1 conditional knockout mice. Our studies further revealed that Rack1 is essential for PF–PC synapse formation. In addition, Rack1 plays a critical role in regulating synaptic plasticity and long-term depression (LTD) induction of PF–PC synapses without changing the expression of postsynaptic proteins. Together, we have discovered Rack1 as the crucial molecule that controls PF–PC synaptogenesis and synaptic plasticity. Our studies provide a novel molecular insight into the mechanisms underlying the neural development and neuroplasticity in the cerebellum.